2023
DOI: 10.1002/mma.9128
|View full text |Cite
|
Sign up to set email alerts
|

An existence result with numerical solution of nonlinear fractional integral equations

Abstract: By utilizing the technique of Petryshyn's fixed point theorem in Banach algebra, we examine the existence of solutions for fractional integral equations, which include as special cases of many fractional integral equations that arise in various branches of mathematical analysis and their applications. Also, the numerical iterative method is employed successfully to find the solutions to fractional integral equations. Lastly, we recall some different cases and examples to verify the applicability of our study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…For its numerical solution, they also suggested an iterative approach based on the midpoint rule. We shall demonstrate the falsity of Theorem 5.1 in [12] in this note, among others. We further show that, generally speaking, the recursive connection described in [12] is untrue since sentences in the recursion sequence cannot be calculated from previously unknown phrases; the method can only be used in a specific situation, and the midpoint rule is not good at all to find numerically a fixed point of equation ( 2) in fractional cases (0 < τ < 1); instead, using Jacobi's quadrature rule works well.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…For its numerical solution, they also suggested an iterative approach based on the midpoint rule. We shall demonstrate the falsity of Theorem 5.1 in [12] in this note, among others. We further show that, generally speaking, the recursive connection described in [12] is untrue since sentences in the recursion sequence cannot be calculated from previously unknown phrases; the method can only be used in a specific situation, and the midpoint rule is not good at all to find numerically a fixed point of equation ( 2) in fractional cases (0 < τ < 1); instead, using Jacobi's quadrature rule works well.…”
Section: Introductionmentioning
confidence: 63%
“…The goal of article [12] is to examine in order to determine fixed points of equation ( 2) and a subjected iterative method to solve numerically it if the conditions are considered appropriate for all continuous functions in (3) (refer to [12, conditions (1)-(3)]). Consequently, Kazemi et al [12] demonstrated the existence of a fixed point for T using Petryshyn's theorem. For its numerical solution, they also suggested an iterative approach based on the midpoint rule.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the research underscored the Newton-Raphson method's robustness, as it consistently converged efficiently with minimal iteration counts across various benchmark problems. This underscored the method's superiority in terms of efficiency and reliability, especially when dealing with complex nonlinear equations [21].…”
Section: Related Workmentioning
confidence: 99%
“…Example 2.6. Kazemi et al [18] used the following conditions to check the fixed point existence solution of fractional integral equation z = T z, where…”
Section: Case Studymentioning
confidence: 99%
“…Thus, (II)-(III) hold and equation ( 13) has a fixed point solution in B ρ (E). Also, from (II) it is needed to add conditions [18] and compare with (4)).…”
Section: Case Studymentioning
confidence: 99%